Climate Security Investment Planning: A methodology to co-develop investments with climate action and peacebuilding objectives - Savelli, Adam; Medina, Leonardo; Chilambe, Pedro Anglaze; Meddings, George; Sarzana, Carolina; Achicanoy Estrella, Harold Armando; Mendez Alzate, Andres Camilo; Jaquet, Stéphanie; Pacillo, Grazia; Läderach, Peter R.D.; Girvetz, Evan Hartunian (CGIAR FOCUS Climate Security, 2022)
Finance for climate action can be an important means of bolstering the resilience of communities exposed to climate hazards, addressing developmental challenges, and redistributing wealth toward the Global South. However, investments in contexts where climate and conflict risks overlap must recognize linkages between the two and be careful not to cause or worsen violence. More aspirationally, they should leverage food, land, and water systems to build peace by fostering positive social conditions. Toward that goal, this document articulates a process to identify, co-develop, and deploy integrated climate security investments.